Simian adenoviruses as vaccine vectors. (September 2016) - Morris, Susan J; Sebastian, Sarah; Spencer, Alexandra J; Gilbert, Sarah C
Replication incompetent human adenovirus serotype 5 (HAdV-C5) has been extensively used as a delivery vehicle for gene therapy proteins and infectious disease antigens. These vectors infect replicating and nonreplicating cells, have a broad tissue tropism, elicit high immune responses and are easily purified to high titers. However, the utility of HAdV-C5 vectors as potential vaccines is limited due to pre-existing immunity within the human population that significantly reduces the immunogenicity of HAdV-C5 vaccines. In recent years, adenovirus vaccine development has focused on simian-derived adenoviral vectors, which have the desirable vector characteristics of HAdV-C5 but with negligible seroprevalence in the human population. Here, we discuss recent advances in simian adenovirus vaccine vector development and evaluate current research specifically focusing on clinical trial data.